Production of a Botanical Spirit Resembling Gin Using a Manual Distillation Method as an Innovation in Spirit-Based Beverage Products in the Food and Beverage Field - Felicia Tan; Vasco A.H. Goeltom; Kevin Gustian Yulius (Jurnal Ilmu Multidisiplin, 2026)
This study aims to develop a gin-style botanical spirit using a manual distillation method as an innovation in spirit-based beverage products within the food and beverage sector. The research focuses on formulating alternative botanicals without the use of juniper berry, evaluating sensory characteristics, and measuring alcohol content. A Research and Development (R&D) approach was employed, consisting of stages including product design, design validation, product testing, revision, and dissemination. The botanicals used included pink peppercorn, black pepper, coriander seed, dried lemongrass, pandan leaf, lemon peel, and orange peel. These botanicals were extracted through a short maceration process followed by manual distillation using a simple pot still. Product evaluation was conducted through organoleptic testing covering color, aroma, taste, and mouthfeel using a four-point Likert scale, along with alcohol content measurement using a hydrometer. The results indicate that the developed formulation successfully produced a gin-style botanical spirit with a balanced citrus, spicy, and herbal aroma profile, good clarity, and a smooth mouthfeel. The alcohol content was within the standard range for distilled spirits, indicating that the product is suitable and safe for application in bar practices. This study is expected to contribute as an academic and practical reference for the development of house-made spirits using manual distillation methods in the bar industry.